Taxonomy of Prorocentrum sp. sampled from Hai Phong city by basing on the nucleotide sequences of the 18S rDNA and ITS1-5.8S-ITS2 gene fragments - Hong, Dang Diem; Hien, Hoang Minh; Anh, Hoang Lan; Thuoc, Chu Van (Academia Journal of Biology, 2006)
The nucleotide sequences of the 18S rDNA and ITS1-5.8S-ITS2 gene fragments were determined in Prorocentrum sp., which was collected from Hai Phong city, Vietnam in 2004. The length of the 18S rDNA and ITS1-5.8S-ITS2 gene fragments in Prorocentrum sp. were 1059 bp and 657bp, respectly. By comparing the Prorocentrum sp. sequence data with the published sequences of P. lima, P. arenarium, P. maculosum, P. concavum, P. panamensis, P. micans, P. minimum, P. mexicanum, P. emarginatum and P.triestinum in the GeneBank and constructing the phylogenetic tree, the phylogenetic relationships between Prorocentrum sp. and the ten other Prorocentrum species were established. The classification of Prorocentrum species based on the 18S rRNA gene coincided with the classification based on the ITS1-5.8S-ITS2 gene. The results showed that the genetic distances between the species within these two groups were low. The similar of these Prorocentrum species was 94% and they were divided into two groups. The first group included P. emarginatum. The second group included other species with 2 subgroups; the first subgroup included P. arenarium, P. lima, P. maculosum, P. concavum and P. panamensis and the second subgroup included Prorocentrum sp., P. mexicanum, P. micans and P. minimum. Among these species, Prorocentrum sp. had a close phylogenetic relationship with P. mexicanum (99.9%). The morphological characteristics of Prorocentrum sp. also showed a relatively high similarity with P. mexicanum. It has been shown that Prorocentrum sp. collected from Haiphong belonged to the species P. mexicanum. The nucleotide sequence of the ITS1-5.8S-ITS2 gene fragments of P. mexicanum (collected from Hai Phong) was submitted to the GeneBank with accession number-AY886 763.